Creutzfeldt-Jakob disease presenting as psychiatric disorder: case presentation and systematic review - Huang, Brendan; Shafiian, Neeva; Masi, Paul Joseph; Gordon, Marc L.; Franceschi, Ana M.; Giliberto, Luca (Frontiers in Neurology, 2024)
Creutzfeldt-Jakob disease (CJD) is a spongiform encephalopathy caused by misfolded human prion proteins (PrP)s. Due to variability in presentation, the diagnosis may be missed in lieu of various psychiatric disorders. Our study reports on a prototypical case and psychiatric mimics for CJD, and the workup used to establish the correct diagnosis. A 54-year-old male with a past medical history of traumatic brain injury and major depressive disorder presented with chest pain. During the hospital stay, he was found to be increasingly aggressive, and behaved out of character. Further review of clinical history revealed that the patient was diagnosed with cognitive impairment and depression one year prior. The patient was agitated, poorly redirectable, and had unstable gait on neurological examination. Magnetic resonance imaging (MRI) of the brain demonstrated restricted diffusion (DWI) along the parietooccipital and temporal regions (L>R) and in the subcortical structures, including the basal ganglia and thalami, with accompanying subtle fluid attenuation inversion recovery (FLAIR) hyperintense signal abnormality in these regions, deemed as artifactual at the time. Repeat MRI brain two months later demonstrated progression of the DWI signal with ADC correlate and FLAIR findings. Cerebrospinal fluid 14-3-3 and RT-QuIC samples were positive. Upon passing a few months later, brain autopsy and Western Blot confirmed the CJD diagnosis.Literature review was conducted on PubMed to identify CJD cases initially diagnosed as psychiatric disorder. Search terms included "CJD" or "Creutzfeldt-Jakob disease" with three common psychiatric diagnoses, "Depression," "Psychosis," and "Mania." Positive EEG, MRI, PET, and CSF (including protein 14-3-3 and tau) findings for CJD were found in 66.7%, 81.1%, 50%, and 72.7% of cases respectively. CJD can present as a psychiatric mimic. In suspicious cases, EEG, imaging, and CSF studies should be promptly utilized to arrive at the correct diagnosis. Repeated MRI imaging is often required to help in the diagnostic process. Brain biopsy should be considered in selected cases.